Analysis of the Vulnerability Model for Decision-Making in the Field of Care for the Elderly - Fabio Nacimento DaSilva (International Journal of Science and Society, 2020)
This article analyzes the validity of vulnerability as a model for decision making regarding the personal and socio-family situation of the elderly person in need of care. The adequacy of the model responds to the centrality of the risk element in decision-making, the nature of care and respect for the principles that inspire the rights of vulnerable older persons. The concept of vulnerability connects with a new conception in which vulnerability is based, not only on the loss of autonomy, but also on the susceptibility to bankruptcy of the rights of dignity and integrity in daily life; in line with an existentially diverse and vulnerable human conception. The incorporation of this approach to the Law of the capacity of the elderly and regulation of social services will require its consideration in the reports and diagnoses of Social Work.